1994
DOI: 10.1016/s0022-5223(94)70337-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diltiazem on perioperative ischemia, arrhythmias, and myocardial function in patients undergoing elective coronary bypass grafting

Abstract: A prospective, randomized study was performed on 120 patients undergoing elective coronary bypass grafting to define the effect of the calcium channel blocker diltiazem on perioperative ischemia, arrhythmias, and myocardial function. Patients received a continuous 24-hour perioperative infusion of either diltiazem (0.1 mg/kg per hour, n = 60) or nitroglycerin (1 ltg/kg per minute, n =60). Perioperative monitoring included hemodynamic measurements, three-channel Holter monitoring, repeated assessment of 12-lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…In order to protect the myocardium from ischemic damage, various protective measures have been introduced during recent years such as systemic and local hypo-thermia, anti-and/or retrograde hypothermic crystalloid or blood cardioplegia, and recently, warm blood cardioplegia [8][9][10][11]. Clinical studies have demonstrated the significant antiischemic and antian'hythmic protection of continuous infusion of calcium antagonist diltiazem for patients undergoing coronary bypass grafting [2][3][4][5]. Perioperative calcium antagonist infusion appears to be remarkably effective in improving myocardial protection during and after coronary bypass surgery [t2,13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to protect the myocardium from ischemic damage, various protective measures have been introduced during recent years such as systemic and local hypo-thermia, anti-and/or retrograde hypothermic crystalloid or blood cardioplegia, and recently, warm blood cardioplegia [8][9][10][11]. Clinical studies have demonstrated the significant antiischemic and antian'hythmic protection of continuous infusion of calcium antagonist diltiazem for patients undergoing coronary bypass grafting [2][3][4][5]. Perioperative calcium antagonist infusion appears to be remarkably effective in improving myocardial protection during and after coronary bypass surgery [t2,13].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, increasing numbers of patients with more severe coronary artery disease and impaired left ventricular function demand further improvements in perioperative patient management. In previous clinical studies we could demonstrate the significant antiischemic and antiarrhythmic protection of continuous infusion of calcium antagonist diltiazem in patients undergoing coronary bypass grafting [2][3][4][5]. However, prevention of perioperative ischemic events may predict a lower incidence of myocardial infarction or reappearance of angina during postoperative followup, as has been shown for variant or unstable angina in patients with coronary artery disease [6,7].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…A number of studies have reported that administration of diltiazem before or during I/R reduces infarct size and protects against reperfusion injury (Klein et al ., 1984; Seitelberger et al ., 1994; Tadokoro et al ., 1996). The beneficial effects of diltiazem on ischemic myocardium are generally thought to be due to coronary artery vasodilatation and a decrease of heart rate as well as cardiac contractility (Ferrari and Visioli, 1991).…”
Section: The Endothelium As a Target For Cardioplegic Solutionsmentioning
confidence: 99%